2018
DOI: 10.1007/s10899-018-9789-4
|View full text |Cite
|
Sign up to set email alerts
|

Doing It for the Money: The Relationship Between Gambling and Money Attitudes Among College Students

Abstract: Today's college students have grown up with legalized gambling and access to a variety of gambling venues. Compared to the general adult population, rates of disordered gambling among college students are nearly double. Previous research suggests that the desire to win money is a strong motivator to gamble (Neighbors et al. in J Gambl Stud 18:361-370, 2002a); however, there is a dearth of literature on attitudes towards money in relation to gambling behavior. The current study evaluated the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…All the above features result in financial vulnerability and helplessness in everyday life. Be in tune with results of Grohs-Müller and Greimel-Fuhrmann (2018) anxious spenders decisions are more emotionally and anxiety attitudes relate positively to gambling behavior (Larimer, 2018). Therefore young people should be considered as a crucial target group of financial education, their purchase behaviour and access to money have changed remarkably during the last few decades (Fraczek and Klimontowicz, 2018).…”
Section: Discussionmentioning
confidence: 81%
“…All the above features result in financial vulnerability and helplessness in everyday life. Be in tune with results of Grohs-Müller and Greimel-Fuhrmann (2018) anxious spenders decisions are more emotionally and anxiety attitudes relate positively to gambling behavior (Larimer, 2018). Therefore young people should be considered as a crucial target group of financial education, their purchase behaviour and access to money have changed remarkably during the last few decades (Fraczek and Klimontowicz, 2018).…”
Section: Discussionmentioning
confidence: 81%
“…Another avenue for future research is to examine individual differences in attitudes towards money and objective financial success as antecedents of financial motives that may help explain some of the substantial heterogeneity among the effect sizes (see Table 1). For instance, there is some evidence that people who view money as an important indicator of success, prestige, and power are more likely to gamble and to have gambling problems (4,46). Likewise, the extent to which people hold a financially focused self-concept (i.e., placing overriding importance on financial success for self-definition and self-worth; ,47) and feel financially deprived relative to others (personal relative deprivation; ,48) have both been linked with gambling for financial gain and having gambling problems (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Phau and Woo, 2008; Roberts and Jones, 2001; Taneja, 2012; Yang and Lester, 2002) have replicated the factor structure of the money attitudes scale. Yamauchi and Templers’ scale has been used with college students to explore relationships between money attitudes and a variety of variables, for example, frequency, quantity, consequences and problem severity of gambling (Lostutter et al , 2019); credit card use and misuse (Roberts and Jones, 2001; Watson, 2009); compulsive and impulsive buying (Roberts and Jones, 2001; Watson, 2009); locus of control (Watson, 2009); ethnicity (Medina et al , 1996); personality factors (Norvilitis et al , 2006), personal needs, social identity and emotions (Wong, 2010) and was found to have acceptable reliability and predictive validity.…”
Section: Methodsmentioning
confidence: 99%